Social Conflicts in Multicultural Organisations - Słaboń, Andrzej (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The article analyses the impact of cultural differentiation on the causes and dynamics of social conflicts in organisations. Cultural differentiations are an important factor in social interpretation processes and when constructing a definition of a situation, and are therefore a source of disagreement and social conflict among employees. On the other hand, cultural differences can make social mobilisation difficult and decrease the probability of open conflicts occurring even in the face of strong deprivation. It is important to recognise ways in which organisations protect themselves against inner conflict due to ethnic, national and religious differences. An organisation’s culture and code of "political correctness" seem to be important factors in this context. The article shows different types of multicultural organisations and analyses the impact organisational structure has on the causes and course of conflicts. The simultaneous occurrence of cultural differentiation and deprivation in the sphere of authority are main circumstances that generate social conflict in multicultural organisations.